A New Approach to Secure and Manage Load Balancing of the Distributed Database Using SQL Firewall - A., Fairuzullah; Noraziah, Ahmad; Wan Maseri, Wan Mohd; Herawan, Tutut
This paper is the current approach database security of organization need layers of security around their data, with each layer protecting a specific area. The current trend of security attack is targeting any valuable data stored in a database such as financial data and student mark, including data theft, data modification or replay and data disruption. To understand how the system works, the system setting and the weaknesses of Enterprise Distributed Database. This paper is about the design and development to secure database access, a framework based on packet and content filtering on IP address, port and SQL statement. And simulate the framework and design database security framework. We address how to build the outcome of this is to reduce the risk of data manipulation and reduce the impact of internal threat and malicious insiders. The result shows that the proposed method succeeded in meeting those aspects of information security.